Climate change, resulting natural disasters and the legal responsibility of states : an international law perspective / Alexandra Birchler. - Birchler, Alexandra (Intersentia, 2020)
Extreme weather events, such as cyclones and hurricanes, are increasing in their frequency and intensity. This increase has been scientifically linked to global warming, which is induced by anthropogenic climate change. This phenomenon is disproportionately affecting developing States, such as the Caribbean and Pacific Islands, even though they are not contributing to climate change to the same extent as developed States or emerging markets, and having a devastating effect on people and their livelihoods. This book examines two critical aspects of this situation, to which no specific, singular source in public international law is applicable or responsible. This book first examines the manner in which public international law, in particular international environmental law and customary public international law, is applicable to the question of funding for reconstruction and early warning systems by developed States and emerging markets. As the intensity and frequency of these events increases, so does the requirement for funding, with the aim of improving vulnerable States' resilience to climate-related devastation. While there are several schemes in place in order to secure funding for either early warning systems or postdisaster reconstruction, such as donations or insurance solutions, there is no specific instrument in public international law that deals with the question of whether developed States and emerging markets have an obligation to financially assist disaster-prone developing States with regard to the establishment of early warning systems and reconstruction in the wake of natural disasters. This book also analyses the right to receive humanitarian assistance and the State's obligation to provide early warning. In the aftermath of a calamitous event, the victims are largely dependent on the Sate and its capacity to organise and accept, if necessary, international humanitarian assistance. If the affected State refuses to do so, the consequences for the victims can be disastrous. With regard to humanitarian assistance, the book focuses on the application of human rights law on the international as well as regional levels, such as the African human rights system for example. In addition, the book outlines the doctrine of the responsibility to protect in this context and its practical limits in particular. As concerns the question of whether there is an obligation to provide early warning, this is assessed through an analysis of the case law of the European Court of Human Rights, also taking into account the jurisprudence of the Inter-American Human Rights system. Throughout its discussion of legal responsibility under international law resulting from climate change-induced natural disasters, this book takes into account the new developments around the International Law Commission's project on the Protection of Persons in the Event of Disasters"